Ovarian carcinoma in our midst - Valdivia Ponce, Eduardo (2015)
In 1691 pelvic malignancies genital we find 23 early carcinomas of the ovary; This carcinoma standing in third place among the gynecological cancers, with an incidence of 1.20 percent. 60.3 percent of patients consulting for the first time within the first 6 months of the onset of symptoms; however all had very advanced stages of the disease. The most common symptoms are pain and "abdominal tumor." In 83 percent the size of the tumor being 15 cms. in diameter. The clinical diagnosis was made in 50 percent. The cytodiagnosis no practical value in ovarian carcinoma. We have only one case of group III cells between 14 extended. Metastases were found in 83 percent of cases. Ascites was present in 60 percent of patients tested by laparotomy. More than 50 percent of neoplasms papilíferos correspond to carcinomas. Ovarian carcinoma causes high mortality; before 2 years they have killed 45 percent of the patients. We have done the treatment (surgery, surgery and radiotherapy) is insufficient. Chemotherapy seems to offer hope, as a palliative treatment for advanced cases.